TALAK PERSPEKTIF SYEKH QUTBHI DAN SYEKH QURAISH SHIHAB - Muhammad Jufri; Rikki Arisandi (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
Sheikh Qutbhi in interpreting the verses of divorce in the interpretation of Fi Zilalil Qur'an is in the form of literature and amaliyah. Presenting the inspirations of the Qur'an, concluding the instructions, presenting the principles and values, and explaining the very vital function of the Qur'an by being moving and containing miracles. In addition to the method adopted by linking one verse to another, the discussion of one verse requires another verse that has a correlation (tahlili) is also needed. Meanwhile, Sheikh Quraish Shihab in interpreting the verses of divorce in the interpretation of Al-Mishbah uses the maudhu'i method by focusing on the theme of a verse which is interpreted in detail and with a hermeneutical approach (nuzuli).